Genetic structure of brazilian populations of triatoma sordida (stal, 1859) (hemiptera, triatominae) by means of chromosomal markers - Madeira, Fernanda Fernandez [UNESP]; Dos Reis, Yago Visinho [UNESP]; De Freitas Bittinelli, Isadora [UNESP]; Delgado, Luiza Maria Grzyb [UNESP]; De Oliveira, Jader [UNESP]; Mendonça, Vagner José; Moreira, Felipe Ferraz Figueiredo; De Azeredo-Oliveira, Maria Tercília Vilela [UNESP]; Da Rosa, João Aristeu [UNESP]; Alevi, Kaio Cesar Chaboli [UNESP] (American Society of Tropical Medicine and Hygiene, 2019)
Triatoma sordida is among the main Brazilian species considered as Chagas disease vectors. The genetic studies are directed mainly to phylogenetic questions because this species possibly have suffered cryptic speciation. Furthermore, there are few studies that analyzed the structure and genetic variability of specimens from Brazil and that showed low genetic diversity and strong genetic structuring of the population samples. Therefore, because of great epidemiological importance of T. sordida and mainly the restriction of genetic characterization of this vector only for populations of Minas Gerais state, this article performs a genetic analysis of the T. sordida from seven different Brazilian states (representing different biomes), by means of cytogenetic markers. All analyzed specimens presents the same cytogenetic characteristics: Early meiotic prophase with several heterochromatic bodies dispersed in the nucleus (CGrich), being one of them formed by the associated sex chromosomes surrounded by some autosomal heterochromatic regions, meiotic metaphase with most autosomal pairs exhibiting a C-heterochromatic block in one chromosomal end (CG-rich), Y sex chromosome fully heterochromatin (AT-rich), and X chromosome may present a small C-block (CG-rich). These results are important because the chromosomal markers enable to confirm and expand the low genetic diversity for all Brazilian states occupied by T. sordida, suggesting that all Brazilian populations were originated from a small ancestral population and possibly dispersed to other biomes by founder effect. In addition, we suggest that T. sordida from Brazil are not suffering cryptic speciation and we confirm the classification of all Brazilian examples as T. sordida sensu stricto.